The Acquisition of Relative Clauses in Cypriot Greek: Production and Comprehension - Theodorou, Elena; Grohmann, Kleanthes K. (My University, 2012)
This paper investigates the development of relative clauses in Cypriot Greek (CG) in particular, young children s comprehension and production of subject relatives (SRs) and object relatives (ORs). A total of thirty-three monolingual children aged between 5 and 9 years acquiring CG as their native language (variety) participated in this study. Two different tasks were used to examine the acquisition of restrictive relative clauses: (i) a Picture Pointing Task, modified from Friedmann and Novogrodsky (2004), was used to investigate the auditory comprehension of SRs and ORs, and (ii) a Preference Task, modified from Novogrodsky and Friedmann (2006), was employed to examine the production of SRs and ORs. Crosslinguistic research provides evidence that children experience difficulties in the acquisition of ORs, whereas this does not seem to be the case for SRs (McKee and McDaniel, 2001; Stathopoulou, 2007). The on-going study on the acquisition of SRs and ORs in CG, the first in the literature for this language variety, so far appears to confirm the difficulty attested for other languages that children display in the acquisition of ORs.
Keywords: Cypriot Greek; Subject relatives; Object relatives; Picture pointing task